Prognostic Value of the Blink Reflex Test in Facial Nerve Palsy Treated with Integrative Traditional Korean Medicine: A Retrospective Study - Bonhyuk Goo; Dahae Kang; Jinkyung Park; Jung-Hyun Kim; Sang-Soo Nam; Yonghyeon Baek (MEDrang Inc., 2024)
Background: Several studies have shown the prognostic value of the blink reflex (BR) test in facial nerve palsy (FNP); however, they are limited by small sample sizes and lack of long-term follow-up. To validate the diagnostic value of the BR test in FNP, a large number of patients were followed up for 1 year. Methods: Medical records of 796 patients with FNP who received an integrative traditional Korean medicine treatment were retrospectively reviewed. The BR test was performed 14 (± 2) days after onset, and recovery was evaluated using House-Brackmann (HB) grading until complete recovery or 1 year after onset. Results: Multivariable Cox regression analysis showed that the presence of ipsilateral early response (R1; hazard ratio [HR], 2.41; p < 0.001) was a significant independent predictive factor for better recovery to HB grade II. R1 (HR, 2.21; p = 0.001) and ipsilateral late response (IR2; HR, 1.88; p = 0.006) were significant independent predictive factors for a higher recovery rate to HB grade I. Conclusion: These findings confirm that the BR test is a valuable tool for prognostic prediction in FNP.